An Elemental Phosphorus Photocatalyst with a Record High Hydrogen Evolution Efficiency. Issue 33 (4th May 2016) - Hu, Zhuofeng; Yuan, Luyan; Liu, Zhifeng; Shen, Zhurui; Yu, Jimmy C.
Abstract: Semiconductive property of elementary substance is an interesting and attractive phenomenon. We obtain a breakthrough that fibrous phase red phosphorus, a recent discovered modification of red phosphorus by Ruck et al., can work as a semiconductor photocatalyst for visible‐light‐driven hydrogen (H2 ) evolution. Small sized fibrous phosphorus is obtained by 1) loading it on photoinactive SiO2 fibers or by 2) smashing it ultrasonically. They display the steady hydrogen evolution rates of 633 μmol h −1 g −1 and 684 μmol h −1 g −1, respectively. These values are much higher than previous amorphous P (0.6 μmol h −1 g −1 ) and Hittorf P (1.6 μmol h −1 g −1 ). Moreover, they are the highest records in the family of elemental photocatalysts to date. This discovery is helpful for further understanding the semiconductive property of elementary substance. It is also favorable for the development of elemental photocatalysts. Abstract : A breakthrough : Fibrous‐phase red phosphorous was used as semiconductor photocatalyst for visible‐light‐driven hydrogen evolution. The phosphorus in micro‐fibrous P/SiO2 and smashed‐fibrous phosphorus showed hydrogen evolution rates of 633 μmol h −1 g −1 and 684 μmol h −1 g −1, respectively. These values are records for elemental photocatalysts.